KUALITAS PELAYANAN DALAM PEMBUATAN AKTA KELAHIRAN MENGGUNAKAN APLIKASI LAYANAN ANANDA SEHAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SUKABUMI 2021-2022 - Nur, Tuah; Sriwahyuni, Rizkiya; Agusti, Rismawati; Andriani, Ayu (LPPM UNSAP & FISIP UNSAP, 2023)
This research study focuses on the problem of population administration services through the Healthy Ananda Service application for issuing birth certificates. Among them are complaints from the public regarding errors in inputting birth certificate data, socialization that has not been optimal, infrastructure that is still lacking, completeness of documents that are not on time or not in accordance with existing SOPs, and the lack of responsiveness of service staff. The theory used in this study is the theory put forward by Zeithaml, et al (1988:23) with 5 dimensions, namely (1) tangibles, (2) reliability, (3) responsiveness, (4) assurance, (5) empathy. This study aims to determine the Quality of Public Services Using the Healthy Ananda Service Application at the Population and Civil Registry Office of the City of Sukabumi in 2021-2022, as well as to find out what the inhibiting and supporting factors are. The method used in this research is descriptive qualitative. The results of this study indicate that based on the five dimensions, namely the first, the tangibles aspect is quite good because there are still deficiencies in terms of infrastructure, such as leaky waiting rooms and narrow parking lots. Then the aspects of reliability, responsiveness, assurance, and empathy show good results.